Warburg effect linked to cognitive‐executive deficits in FMR1 premutation. Issue 10 (22nd June 2016) - Napoli, Eleonora; Song, Gyu; Schneider, Andrea; Hagerman, Randi; Eldeeb, Marwa Abd Al Azaim; Azarang, Atoosa; Tassone, Flora; Giulivi, Cecilia
ABSTRACT: A55–200 CGG repeat expansion in the 5′‐UTR of the fragile X mental retardation 1 ( FMR1 ) gene is known as a premutation. Some carriers are affected by the neurodegenerative disorder fragile X‐associated tremor/ataxia syndrome (FXTAS), primary ovarian insufficiency, and neurobehavioral impairments. Based on the mitochondrial dysfunction observed in fibroblasts and brain samples from carriers, as well as in neurons and brains from a mouse model of the premutation, we evaluated the presence of the Warburg effect in peripheral blood mononuclear cells (PBMCs) from 30 premutation carriers with either a rebalance of the metabolism [increasing glycolysis while decreasing oxidative phosphorylation (oxphos)] or a metabolic amplification (increasing glycolysis while maintaining/increasing oxphos). Deficits in oxphos—more pronounced in FXTAS‐affected subjects—were accompanied by a shift toward glycolysis, suggesting increased glycolysis despite aerobic conditions. Differential proteomics extended these findings, unveiling a decreased antioxidant response, translation, and disrupted extra‐cellular matrix and cytoskeleton organization with activation of prosenescence pathways. Lower bioenergetics segregated with increased incidence of low executive function, tremors, below‐average IQ, and FXTAS. The combination of functional and proteomic data unveiled new mechanisms related to energy production in the premutation, showing the potential of being applicable to other psychiatric disorders to identify endophenotypespecific responses relevant to neurobiology.—Napoli, E., Song, G., Schneider, A., Hagerman, R., Eldeeb, M.A.A.A., Azarang, A., Tassone, F., Giulivi, C. Warburg effect linked to cognitive‐executive deficits in FMR1 premutation. FASEB J. 30, 3334–3351 (2016). www.fasebj.org